The Influence of Data Analytics-Based Approaches in Strengthening Multi-Factor Authentication for E-Commerce Fraud Detection - T, Sivakumar.; B M, Praveen; Pareek, Piyush Kumar (Journal of Neonatal Surgery, 2025)
The rapid development in E-Commerce has made buying easy for many people. So far, it also leases more complicated web scams in Multi-Factor Authentication (MFA) is known as a good solution to keep E-Commerce safe. But early MFA can't keep up with new trickeries. This study aspects of at behaviors analyses similar AI, trend checks, & rapid spotting can make MFA improved at stopping scams on E-Commerce. By characteristicat real performances and false acquisition information, this effort shows how tech boosts MFA choices, wrong alerts, & betters spot-on finds. The news shows accumulation analyses to MFA makes it safer.